Bloodstream infections in patients with hematological malignancies: which is more fatal – cancer or resistant pathogens? - Gedik H; Şimşek F; Kantürk A; Yildirmak T; Arica D; Aydin D; Demirel N; Yokuş O (Therapeutics and Clinical Risk Management, 2014)
Habip Gedik,1 Funda Şimşek,1 Arzu Kantürk,1 Taner Yildirmak,1 Deniz Arica,2 Demet Aydin,2 Naciye Demirel,2 Osman Yokuş2 1Department of Infectious Diseases and Clinical Microbiology, 2Department of Hematology, Ministry of Health Okmeydani Training and Research Hospital, İstanbul, Turkey Background: The primary objective of this study was to report the incidence of bloodstream infections (BSIs) and clinically or microbiologically proven bacterial or fungal BSIs during neutropenic episodes in patients with hematological malignancies.Methods: In this retrospective observational study, all patients in the hematology department older than 14 years who developed febrile neutropenia during chemotherapy for hematological cancers were evaluated. Patients were included if they had experienced at least one neutropenic episode between November 2010 and November 2012 due to chemotherapy in the hematology ward.Results: During 282 febrile episodes in 126 patients, 66 (23%) episodes of bacteremia and 24 (8%) episodes of fungemia were recorded in 48 (38%) and 18 (14%) patients, respectively. Gram-negative bacteria caused 74% (n=49) of all bacteremic episodes. Carbapenem-resistant Gram-negative bacteria (n=6) caused 12% and 9% of Gram-negative bacteremia episodes and all bacteremia episodes, respectively. Carbapenem-resistant Gram-negative bacteria included Acinetobacter baumannii (n=4), Pseudomonas aeruginosa (n=1), and Serratia marcescens (n=1). Culture-proven invasive fungal infection occurred in 24 episodes in 18 cases during the study period, with 15 episodes in ten cases occurring in the first study year and nine episodes in eight cases in the second study year. In 13 of 18 cases (72%) with bloodstream yeast infections, previous azole exposure was recorded. Candida parapsilosis, C. glabrata, and C. albicans isolates were resistant to voriconazole and fluconazole.Conclusion: BSIs that occur during febrile neutropenic episodes in hematology patients due to Gram-negative bacteria should be treated initially with non-carbapenem-based antipseudomonal therapy taking into consideration antimicrobial stewardship. Non-azole antifungal drugs, including caspofungin and liposomal amphotericin B, should be preferred as empirical antifungal therapy in the events of possible or probable invasive fungal infections with an absence of pulmonary findings due to increase azole resistance.Keywords: bloodstream infection, fungemia, bacteremia, carbapenem resistance, azole resistance, antifungal treatment, hematological malignancies, febrile neutropenia